Liquid chromatography - high resolution mass spectrometry screening of Astragalus hamosus and Astragalus corniculatus - Aleksandar Shkondrov; Ilina Krasteva (Pensoft Publishers, 2021)
Astragalus hamosus and Astragalus corniculatus were examined for the presence of flavoalkaloids, acylated and highly glycosylated flavonoids. Non-purified extracts of the overground parts of the species were subjected to ultra-high performance liquid chromatography - high resolution electrospray ionisation mass spectrometry (UHPLC-HRESIMS) analysis and the results were compared to authentic reference substances. A flavoalkaloid of kaempferol was newly identified in an extract of A. hamosus. In addition, three compounds - quercetin and kaempferol flavonoids, acylated with hydroxymethylglutaric acid and alcesefoliside, were found in extracts of A. hamosus and A. corniculatus for the first time.